Chemical Composition of the Essential Oil ofHeracleum persicumSeeds of Iran - (ARMAN) TAHERPOUR, AVAT; YOUSEFIRAD, MOSTAFA; KARIMZADEH, RAMIN (Asian Journal of Chemistry, 2010)
Volatile chemical constituents of the essential oil of Heracleum persicum seeds, which is growing wild in Ardebile, Iran were investigated by GC and GC/MS technique. 29 Compounds, representing 75 % of the total oil were identified and 12 unknown compounds detected. The main components are hexylbutyrate (37.7 %), hexylbutanoate (36.7 %), octylacetate (16.3 %), hexyl-2-methylbutanoate (5.7 %), hexylisobutyrate (4.7 %), hexylhexanoate (4.3 %), heptyl-2-methylbutyrate (2.3 %), n-butylbutanoate (2.25 %), hexylvalerate (1.9 %), octylbutanoate (1.7 %) and linalole (1.5 %).